Reciclagem no âmbito educacional: uma abordagem ciência - tecnologia-sociedade no 5º ano do ensino fundamental - Souza, Ray Ely Nobre e (2021)
This study has as general objective to understand if the Natural Sciences of the 5th year of Elementary School address contents about recycling, articulated with the STS approach and sustainable development. The research was carried out during the second semester of 2020 and the first semester of 2021, with a 5th grade teacher from a Manaus state school as the participating subject. The dissertation is divided into three stages: the construction of theoretical and epistemological bases to help understand and approach the recycling theme; the analysis of Environmental Education approaches to understand the conceptions of the recycling theme that are presented in Brazilian educational documents and; the identification of views on recycling of a 5th grade elementary school teacher. The theoretical foundation was supported, mainly, in the texts of Capra (2006), Latour (2019), Viola (1986), Bourdieu (1983, 1997, 2003, 2004, 2009, 2013), Bazzo (2003), Foucault (1979, 1997, 2002, 2010) and by researchers who approach from the perspective of a Critical Environmental Education, among them Gadotti (2008), Leff (2006), Lima (2009). The methodological approach, with a qualitative approach, uses dialectics as a method for understanding the object of study in its entirety, using documental studies and semi-structured interviews as data collection techniques. Through Discourse Analysis, understanding that discourses are built on the outside, which has a speech and a place that precedes it. It was found that recycling in isolation will not have an impact on students, nor on their experiences. It is necessary to go beyond information, encouraging good practices and this will be possible through the relationship with CTS, Environmental Education and Sustainable Development. Keywords: Recycling. CTS Studies. Critical Environmental Education. Scientific knowledge